Spitzer and Herschel studies of dust in supernova remnants in the Small Magellanic Cloud. Issue 1 (26th April 2022) - Matsuura, Mikako; Ayley, Victoria; Chawner, Hannah; Filipović, M D; Reid, Warren; Priestley, F D; Rigby, Andy; Barlow, M J; Gomez, Haley E
ABSTRACT: With the entire Small Magellanic Cloud (SMC) mapped by the Spitzer Space Telescope and Herschel Space Observatory, we were able to search 8–250 μ m images in order to identify infrared (IR) emission associated with SMC supernova remnants (SNRs). A valid detection had to correspond with known X-ray, H α, and radio emission from the SNRs. From the 24 known SNRs, we made five positive detections with another five possible detections. Two detections are associated with pulsars or pulsar wind nebula, and another three detections are part of the extended nebulous emission from the SNRs. We modelled dust emission where fast moving electrons are predicted to collide and heat dust grains which then radiate in IR. With known distance (62.44 ± 0.47 kpc), measured SNR sizes, electron densities, temperatures from X-ray emission as well as hydrogen densities, the modelling of SMC SNRs is straightforward. If the higher range of hydrogen and electron densities were to be accepted, we would expect almost all SMC SNRs to be detected in the IR, at least at 24 μ m, but the actual detection rate is only 25 per cent. One possible and common explanation for this discrepancy is that small grains have been destroyed by the SNRs shockwave. However, within the uncertainties of hydrogen and electron densities, we find that IR dust emission can be explained reasonably well, without invoking dust destruction. There is no conclusive evidence that SNRs destroy swept-up ISM dust.